Preoperative anxiety in children undergoing elective circumcision: A cross-sectional study in a training and research hospital - Karayagmurlu, Ali; Emin Naldan, Muhammet; Karabulut, Ibrahim (Annals of Medical Research, 2021)
Aim: Limited research has been conducted regarding the symptoms of preoperative anxiety that children exhibit prior to circumcision. The aim of this study is to determine the frequency of preoperative anxiety symptoms in children preparing for circumcision and the associated factors.Materials and Methods: This cross-sectional study included 62 subjects ranging from ages 2-12. A personal information form, which the research team developed, was used to evaluate the socio-demographic and clinical data of the participants. Symptoms of preoperative anxiety were assessed using the modified Yale Preoperative Anxiety Scale.Results: The mean age of the participants was 7.37±2.97 and m-YPAS scores were 56±18.10. Increased preoperative anxiety symptoms were observed in 82.3% (n=51) of circumcised children. Subjects who engaged in certain activities prior to admission exhibited significantly lower m-YPAS scores compared to those who did not (p0.05).Conclusions: The early recognition and management of preoperative anxiety in children expecting circumcision will help clinicians in preventing the potential complications associated with increased preoperative anxiety.